Operational processing of AVHRR data at DFD - Tungalagsaikhan, Padsuren; Günther, Kurt P.; Gesell, Gerhard; Dech, Stefan; Ruppert, Thomas (2003)
The German Remote Sensing Data Centre (DFD) of the German Aerospace Centre (DLR) has been receiving satellite data from the NOAA POES satellites in High Resolution Picture Transmission (HRPT) mode since November 1981 to serve the needs of the national and international user community. After reception of the AVHRR data a standardised preprocessing routine delivers calibrated and navigated data. These level 1 data are used for generating RGB - quicklooks overlaid with coastlines, and so-called media products showing wide parts of Central Europe in predefined annotated map projections. The level 1 data are also used for generating value-added products such as the “Normalised Difference Vegetation Index” of Europe, the sea surface temperature of European seas and the land surface temperature of Europe representing a day-time or night-time land surface temperature. For all value-added products different routines, such as automatic cloud masking using APOLLO software, precise geo-referencing, including land-sea mask and compositing, are necessary (level 2 data). The level 2 data are used for deriving daily, weekly and monthly level 3 products which are accessible by the internet using a user-friendly Web portal. More than 65,000 scenes (as of May 2003) have been received since 1981 at Oberpfaffenhofen covering the station's visibility. Depending on the actual track (eastern, central and western) being received, the scenes cover different areas, reaching from Spitzbergen in the north to the Northern Sahara in the south and from the Central Atlantic in the west to Central Asia in the east. This paper addresses aspects for daily operational processing, including the automatic supervision of the processing chain, for generating level 1 to 3 products , automatic failure identification and quality assurance. Future processing algorithms (automatic atmospheric correction, generation of cloud parameters and LAI time series), which are in a developmental stage, will also be discussed.